2009
DOI: 10.1111/j.1365-2966.2009.14606.x
|View full text |Cite
|
Sign up to set email alerts
|

Dust settling in magnetorotationally driven turbulent discs - I. Numerical methods and evidence for a vigorous streaming instability

Abstract: In this paper, we have used the RIEMANN code for computational astrophysics to study the interaction of a realistic distribution of dust grains with gas at specific radial locations in a vertically stratified protostellar accretion disc. The disc was modelled to have the density and temperature of a minimum mass solar nebula, and shearing box simulations at radii of 0.3 and 10 au are reported here. The disc was driven to a fully developed turbulence via the magnetorotational instability (MRI). The simulations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 68 publications
5
68
0
Order By: Relevance
“…Youdin & Johansen (2007) and Johansen et al (2007) confirmed that this instability is able to produce very dense dust clumps and leads to rapid planetesimal formation. This result was later confirmed by high resolution numerical simulations (Johansen et al 2011), as well as by other authors using different methods and codes (Balsara et al 2009;Tilley et al 2010;Bai & Stone 2010a;Jacquet et al 2011;Kowalik et al 2013).…”
Section: Introductionsupporting
confidence: 59%
“…Youdin & Johansen (2007) and Johansen et al (2007) confirmed that this instability is able to produce very dense dust clumps and leads to rapid planetesimal formation. This result was later confirmed by high resolution numerical simulations (Johansen et al 2011), as well as by other authors using different methods and codes (Balsara et al 2009;Tilley et al 2010;Bai & Stone 2010a;Jacquet et al 2011;Kowalik et al 2013).…”
Section: Introductionsupporting
confidence: 59%
“…It is conceivable that there are two populations of dust grains, with one responsible for polarization, the other for β. The two populations do not have to be located co-spatially in the disk; for example, large grains responsible for the bulk of the unpolarized continuum (and thus β) may have set-tled close to the midplane, whereas smaller grains that dominate the polarized millimeter radiation may remain floating higher up above the midplane (e.g., Dullemond & Dominik 2004;Tanaka et al 2005;Balsara et al 2009 ). If this speculation turns out correct, polarized emission in millimeter would provide a powerful probe of not only grain growth, but also the expected vertical stratification of grain sizes, especially in conjunction with observations of optical/IR polarization, which probe even smaller, micron-sized, grains that are higher up still above the disk midplane.…”
Section: Opacity Spectral Index β and The Need For Largermentioning
confidence: 99%
“…Hence, streaming instability may be responsible for the Initial Mass Function of planetesimals in discs (Simon et al 2016;Schäfer et al 2017). The robustness of the streaming instability has been tested against several numerical schemes (Balsara et al 2009;Miniati 2010;Tilley et al 2010;Bai & Stone 2010a;Johansen et al 2012Johansen et al , 2014, towards the aim of simulating its E-mail: mailto:guillaume.laibe@ens-lyon.fr effect in a global disc (Lyra & Kuchner 2013;Kowalik et al 2013;Yang & Johansen 2014). Other physical processes such as vortices (Raettig et al 2015), photo-evaporation (Carrera et al 2017), presence of small grains (Laibe & Price 2014), grain growth (Drażkowska & Dullemond 2014) or snow lines (Schoonenberg & Ormel 2017) may reinforce the ability of streaming instability to concentrate dust.…”
Section: Introductionmentioning
confidence: 99%